2018
DOI: 10.1002/fsn3.801
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition and glycemic index analyses of vitamin A‐biofortified maize in healthy subjects

Abstract: Besides being a veritable tool for easing the problem of vitamin A deficiency (VAD), this study sought to explore another potential health benefit of vitamin A‐biofortified maize (VABM). In the present study, the nutritional composition and glycemic index (GI) of tuwo masara (a nonfermented maize‐based dumpling), made from VABM and the indigenous white maize (IWM) genotype, were evaluated. VABM showed significantly (p < 0.05) lower fat (4.38 ± 0.46%) and crude protein (6.58 ± 0.13%) but higher crude fiber (5.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This result is obviously because the protein content in white maize was not significantly different from PVA-biofortified maize. In contrast, Pillay et al found that PVA-biofortified maize had a higher protein concentration than white maize [60], whereas Oluba and Oredokun-Lache found that white maize had a significantly higher value than PVA-biofortified maize [62]. The reason for the differences seen in protein concentration could be attributed to genetic and/or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…This result is obviously because the protein content in white maize was not significantly different from PVA-biofortified maize. In contrast, Pillay et al found that PVA-biofortified maize had a higher protein concentration than white maize [60], whereas Oluba and Oredokun-Lache found that white maize had a significantly higher value than PVA-biofortified maize [62]. The reason for the differences seen in protein concentration could be attributed to genetic and/or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecule is the same, once supplied through a food matrix, the digestion and absorption rate in the gastrointestinal tract is lower [59]. This condition is extremely interesting and desirable for food products that can be consumed by people with chronic diseases such as obese and diabetics individuals [60][61][62][63].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have already demonstrated that phenolic substances have antimicrobial, antioxidant, antiviral, anti-inflammatory, and vasodilatory properties (Thirumurugan et al, 2018). For carotenoids, antioxidant properties, protection against oxidative damage to cellular components, prevention of cardiovascular diseases and cancer are described (Oluba & Oredokun-Lache, 2018). Therefore, the consumption of foods that are sources of these substances results in health benefits and contributes to an improved quality of life (Castejón-Veja et al, 2020).…”
Section: Resultsmentioning
confidence: 99%